Four hour work week: Escape the nine to five live anywhere and join the new rich - Timothy Ferriss; FERRISS (Timothy) (London Vermillion, 2011)
How to reconstruct your life? Whether your dream is experiencing high-end world travel, earning a monthly five-figure income with zero management, or just living more and working less, this book teaches you how to double your income, and how to outsource your life to overseas virtual assistants for $5 per hour and do whatever you want.
Keywords: Definition; Elimination; Automation; Liberation